2007
DOI: 10.1007/s11661-007-9197-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molybdenum and Vanadium Addition on Tensile and Charpy Impact Properties of API X70 Linepipe Steels

Abstract: This study is concerned with the effects of V and Mo addition on tensile and Charpy impact properties of API X70 linepipe steels. Twelve kinds of steel specimens were produced by varying V and Mo additions and rolling conditions. The addition of V and Mo promoted the formation of acicular ferrite (AF), banitic ferrite (BF), and martensite-austenite (MA) constituents, while suppressing the formation of polygonal ferrite (PF) or pearlite (P). The tensile test results indicated that the tensile strength of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Additionally, it was found in many TEM observations that AF laths contain a higher density of dislocations than those associated with reconstructive transformation products [12,[42][43][44], and the AF microstructure consists of several parallel subunits with a size less than 1 lm [12,42] resembling the sheaf morphology of bainitic ferrite [5]. In summary, AF shows similar transformation behaviours and microstructure characteristics to those of bainite; therefore, it is reasonable to say that the AF transformation mechanism is in fact bainitic, which is also agreed by many other researchers [2,3,12,[44][45][46].…”
Section: Discussion Acicular Ferrite Transformation Mechanismsupporting
confidence: 74%
“…Additionally, it was found in many TEM observations that AF laths contain a higher density of dislocations than those associated with reconstructive transformation products [12,[42][43][44], and the AF microstructure consists of several parallel subunits with a size less than 1 lm [12,42] resembling the sheaf morphology of bainitic ferrite [5]. In summary, AF shows similar transformation behaviours and microstructure characteristics to those of bainite; therefore, it is reasonable to say that the AF transformation mechanism is in fact bainitic, which is also agreed by many other researchers [2,3,12,[44][45][46].…”
Section: Discussion Acicular Ferrite Transformation Mechanismsupporting
confidence: 74%
“…Despite the unique morphology of AF, many investigations have shown that the transformation mechanism of AF is similar to that of BF. [8][9][10][11][12][13] As for the grain refinement of low-temperature transformation products, although the effect of austenite deformation has been studied by many researchers, the results are still controversial. In a prior investigation, [14] it was shown that the effective grain size of bainite increases from 3.2 to 3.8 lm when austenite was deformed by 30 pct.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the microstructure of microalloyed steels with a view to improving their mechanical properties had been conducted by many researchers. [8][9][10] Steels used for large-scale structures, such as the tower flanges of wind turbines, are usually produced by hot forging followed by air cooling. For meeting the structural safety requirements, such structural steels require excellent strength to bear static and dynamic heavy loads.…”
Section: Jingwei Zhao Taekyung Lee Jeong Hun Lee Zhengyi Jiang Anmentioning
confidence: 99%